Habitat suitability modelling and range change dynamics of Bergenia stracheyi under projected climate change scenarios - Wani, Zishan Ahmad; Dar, Javid Ahmad; Lone, Aamir Nazir; Pant, Shreekar; Siddiqui, Sazada (Frontiers in Ecology and Evolution, 2025)
Prioritizing native and endemic species for conservation is fundamental to achieve broader objectives of safeguarding biodiversity, as these species are vulnerable to extinction risks. Forecasting the climatic niche of these species through species distribution models can be crucial for their habitat conservation and sustainable management in future. In this study, an ensemble modelling approach was used to predict the distribution of Bergenia stracheyi, a native alpine plant species of Himalayan region. The results revealed that the distribution of B. stracheyi is primarily influenced by Annual Mean Temperature (Bio1) and Annual Precipitation (Bio12). Ensemble model predictions revealed that under the current climatic conditions, the suitable habitats for B. stracheyi are distributed across higher elevations of Jammu and Kashmir and future ensemble model predictions indicate that, across all future climatic scenarios, the majority of the currently suitable habitats will remain suitable for the species. The model predicts a significant expansion in suitable habitats for B. stracheyi, particularly under more severe climate change scenarios (RCP8.5). However, some areas currently identified as suitable, including parts of the Pir Panjal range and Mirpur (Pakistan), are projected to become unsuitable for the species in the future. These shifts in plant distribution may have far-reaching consequences for ecosystem functioning and stability and the services provided to human communities. Additionally, these shifts may lead to mismatches between the plant phenological events and pollinators potentially causing more ecological disruptions. Thus, the predicted range shifts in the distribution of B. stracheyi highlight the importance of local conservation measures to mitigate the impacts of climate change.